Find
x
,
y
,
z
satisfying the equations
⎩
⎪
⎪
⎨
⎪
⎪
⎧
(
x
+
y
)
(
x
+
y
+
z
)
=
6
6
(
y
+
z
)
(
x
+
y
+
z
)
=
9
9
(
z
+
x
)
(
x
+
y
+
z
)
=
7
7
Submit your answer as the sum of all possible values of ( x + y + z ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Alternate solution:
Since
(
x
+
y
+
z
)
is common in all the equations,we can easy predict that
x
+
y
+
z
=
±
1
1
.
(because
±
1
1
is divisible in all the equations.So the sum of all possible values of
(
x
+
y
+
z
)
=
1
1
−
1
1
=
0
.
Problem Loading...
Note Loading...
Set Loading...
Adding the three equations, we get
2 ( x + y + z ) 2 = 2 4 2 or ( x + y + z ) 2 = 1 2 1 ⇒ ( x + y + z ) 2 = ± 1 1 .
Therefore the sum of all possible values of ( x + y + z ) = 1 1 − 1 1 = 0 .